2019
DOI: 10.1002/aenm.201901938
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Interfacial Dipoles to Minimize Open‐Circuit Voltage Loss in Quantum Dot Photovoltaics

Abstract: Quantum‐dot (QD) photovoltaics (PVs) offer promise as energy‐conversion devices; however, their open‐circuit‐voltage (VOC) deficit is excessively large. Previous work has identified factors related to the QD active layer that contribute to VOC loss, including sub‐bandgap trap states and polydispersity in QD films. This work focuses instead on layer interfaces, and reveals a critical source of VOC loss: electron leakage at the QD/hole‐transport layer (HTL) interface. Although large‐bandgap organic materials in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…[80,81] While this approach showed promising results, the stability of the transport layers needs to be improved further. [82][83][84][85][86][87][88] Another interesting passivation route involves the introduction of a layer of carbon nanotubes between the EDT layer and the gold anode, as reported by Salazar-Rios et al [74] in 2018. It was found that a single-walled carbon nanotube (SWCNT) layer significantly improved cell stability under illumination, which maintained 85% of its initial PCE after 105 h of continuous In the pristine state (before oxygen exposure) surface traps are present, so charge recombination between dots is uninhibited and leakage pathways remain open.…”
Section: Degradation Of Charge Extraction Layers In Solar Cellsmentioning
confidence: 99%
“…[80,81] While this approach showed promising results, the stability of the transport layers needs to be improved further. [82][83][84][85][86][87][88] Another interesting passivation route involves the introduction of a layer of carbon nanotubes between the EDT layer and the gold anode, as reported by Salazar-Rios et al [74] in 2018. It was found that a single-walled carbon nanotube (SWCNT) layer significantly improved cell stability under illumination, which maintained 85% of its initial PCE after 105 h of continuous In the pristine state (before oxygen exposure) surface traps are present, so charge recombination between dots is uninhibited and leakage pathways remain open.…”
Section: Degradation Of Charge Extraction Layers In Solar Cellsmentioning
confidence: 99%
“…Interface recombination and low stability remain the major bottlenecks of electron-blocking and hole-transport layers. 33,34 Previously, we fabricated approximately 1 μm-long ZnO nanowires (NWs) and constructed heterojunction CQD solar cells without any particular EBLs; the solar cell was composed of a PbS QD−ZnO NW interdigitated layer sandwiched between a transparent conductive oxide layer and a Au electrode 37,38 (Figure 1b). The longer NWs produce higher EQE in the infrared region.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It was also reported that the insertion of a molecular dipole layer at the interface of the p-and n-type materials can shift the relative band position to enhance the Vph [15,16]. Wick-Joliat et al recently elucidated that the insertion of phosphonic acid dipole layer at Si/TiO2 can significantly improve the onset potential of Si photocathode up to 400 mV as supported by both theoretical calculation and experimental observation [17].…”
Section: Introductionmentioning
confidence: 86%